Genome editing and its applications in genetic improvement in aquaculture - Zituo Yang; Yepin Yu; Yi Xuan Tay; Gen Hua Yue (John Wiley & Sons Australia, Ltd, 2025)
In the aquaculture industry, selective breeding has played an important role in increasing aquaculture production significantly. To meet the global growing demand for high quality proteins, it is essential to apply novel technologies to accelerate breeding to facilitate the increase in aquaculture production. Gene and genome editing technologies, including ZFNs, TALLENS and Crispr/Cas9, are promising tools to speed up genetic improvement. Among all the genome editing approaches, the CRISPR/Cas9 system is faster, cheaper and precise in editing genes/genomes. Therefore, the application of CRISPR/Cas9 technology in the editing of genomes in aquaculture species is emerging rapidly. It has been applied to precisely edit genes to identify gene functions and generate the preferred traits in over 20 aquaculture species. This review summarises the genome editing technologies and their applications in the rapid improvement of economic traits in the aquaculture industry. Challenges and future directions of genome editing are also discussed.